2023
DOI: 10.1093/jas/skac345
|View full text |Cite
|
Sign up to set email alerts
|

Post-weaning management of modern dairy cattle genetics for beef production: a review

Abstract: The contribution of dairy steers to the U.S. fed beef supply has increased from 6.9% to 16.3% over the last two decades; in part, due to declining beef cow numbers and the increased use of sexed dairy semen to produce genetically superior replacement heifers from the best dairy cows. Raising dairy cattle for beef production offers unique opportunities and challenges when compared with feeding cattle from beef breeds. Dairy steers offer predictable and uniform finishing cattle performance (ADG, DMI, G:F) as a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The Limousin crossbred calves had lower milk consumption (439.3 ± 17.8 L for heifers and 446.3 ± 17.9 L for bulls) compared to the other breed groups. Notably, the Limousin crossbred calves had the lowest milk consumption while having similar weaning weight and ADG compared to the other breed groups, which may be an indicator of heterosis for feed efficiency of beef and dairy crossbreds ( Basiel and Felix, 2022 ; Jaborek et al, 2023 ). Similar to the current study, Vestergaard et al, (2019) reported that ADG was similar for Limousine crossbred heifer and bulls compared to HO bull calves.…”
Section: Resultsmentioning
confidence: 94%
“…The Limousin crossbred calves had lower milk consumption (439.3 ± 17.8 L for heifers and 446.3 ± 17.9 L for bulls) compared to the other breed groups. Notably, the Limousin crossbred calves had the lowest milk consumption while having similar weaning weight and ADG compared to the other breed groups, which may be an indicator of heterosis for feed efficiency of beef and dairy crossbreds ( Basiel and Felix, 2022 ; Jaborek et al, 2023 ). Similar to the current study, Vestergaard et al, (2019) reported that ADG was similar for Limousine crossbred heifer and bulls compared to HO bull calves.…”
Section: Resultsmentioning
confidence: 94%
“…This prob- lem is inherent not only for the domestic livestock industry. For example, the contribution of dairy steers to the U.S. fed beef supply has increased from 6.9% to 16.3% over the last two decades (Jaborek et al, 2023). The production of beef from a dairy herd is not without its challenges (for example, dairy steers have a lower dressing percentage and yield less red meat, and present problems in the beef packing industry).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent advances in genomic technologies ( Crowe et al, 2021 ), reproductive efficiency ( Cardoso Consentini et al, 2021 ), and sex-selected semen ( Hutchison et al, 2016 ) have enabled more precise dairy replacement heifer production and widespread use of beef semen on commercial dairies ( McWhorter et al, 2020 ). Recent reviews by Berry (2021) , Crowe et al (2021) , Basiel and Felix (2022) , Foraker et al (2022) , Poock and Beckett (2022) , and Jaborek et al (2023) emphasize academic interest in beef × dairy crossbred calves. Similarly, selection indexes aimed at optimizing beef semen used in dairy herds by American Simmental Association and American Angus Association summarize interest of the beef industry in the concept of beef × dairy crossbreeding.…”
Section: Introductionmentioning
confidence: 99%